Research and publications in Islamic perspective (part 3: presentation) - Khedher, Akram M Z M (Kulliyyah of Information and Communication Technology, IIUM, 2023)
This article is the 3rd part of the “Research and Publications in Islamic Perspective”, since part 1 was an introductory on this topic, while part 2 was focusing on experimental results of the research. This part focuses on the presentation, which is needed in any research and publication, the presentation of the work should be clear, simple and transparent., in this article we are going to discuss some of these issues from Islamic perspective.